Formulasi Ransum Alternatif Untuk Meningkatkan Efisiensi Usaha Peternakan Sapi Perah (Studi Kasus pada Peternakan Bestcow Farm Jember) - Huda Ahmad Hudori; Hari Rujito; Muksin Muksin; Fredy Eka Ardhi Pratama; Paramita Andini (Jurnal Ilmu Peternakan Terapan, 2020)
This study aimed to examine the formulation of the cheapest alternative dairy rations and analyze the income and cost-efficiency of Bestcow Farm Jember. This research was conducted at Bestcow Farm Jember. The research location was chosen using purposive sampling with the consideration that Bestcow Farm has a fairly large population of dairy cattle, 50 heads. The research parameters taken were alternative ration formulations, income analysis, and cost-efficiency. This research used a descriptive method based on the results of data collection obtained from direct interviews with company employees and Bestcow Farm recording. The alternative ration formulation 2 was an alternative formulation ration with the cheapest price. This alternative ration formulation was feasible to be applied to Bestcow Farm Jember to get higher income.